ANALISIS TREND PERKEMBANGAN PENDAPATAN PEMERINTAH DAERAH KABUPATEN TANAH LAUT TAHUN 2014-2018 - Mufrida Zein; Eni Suasri (Jurnal Riset Akuntansi Politala, 2022)
Regional government revenues consist of several sources, namely regional original revenue funds, balancing funds, and other legal regional income funds. This study uses trend analysis using the percentage method to estimate regional income based on data for 2014-2018. The purpose of this study is to present an overview of the development of regional income in Tanah Laut Regency therefore it can assist the government in realizing a transparent process. Calculations of regional income sources share the revenue of the Tanah Laut district government with a very low trend in 2015. This is due to a deficit in 2015 since the income received is lower than the government's spending. In 2018 there was a Regional Entry with a very large trend. This is since in 2018 there was a surplus, due to greater income than the government's spending.